Estimation of Prestress Loss of Pretensioned Concrete Beam with Different Tendon Profiles at Different Locations - Mishra L.; Singh S.B.; Maiti P.R.; Mohanty S. (My University, 2025)
From the point of load transfer, initial prestress introduced in concrete gradually decreases over time for a variety of reasons. This is generally referred as loss of prestress. This paper investigates the pattern of distribution of prestress losses along the length and cross-sectional dimension of prestressed beam. Emphasis has been made to investigate the effects of tendon profile on distribution of prestress loss along the beam's span. Prestressed concrete beams analyzed in present study includes four typical tendon profiles: (a) straight tendon, (b) triangular, (c) trapezoidal and (d) parabolic tendon. It is concluded from this study that the total prestress losses are not having uniform distribution along the length of a simply supported pretensioned concrete beam and are independent of tendon profiles. Prestress loss due to shrinkage in concrete and relaxation of tendons does not vary along the length instead shrinkage loss varies with cross-sectional dimension of the beam. It is observed that the loss of prestress due to creep of concrete is dominant along the length of beam as compared to elastic deformation and shrinkage losses. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2025.